The Effect of Liquidity on Capital Structure with Company Size as a Moderating Variable Mediated by Profitability: Pengaruh Likuiditas Terhadap Struktur Modal Dengan Ukuran Perusahaan sebagai Variabel Moderasi yang Dimediasi oleh Profitabilitas - Olivia Monica; Wawan Ichwanudin; Emma Suryani (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study aims to examine and analyze the effect of liquidity on capital structure, with firm size as a moderating variable and profitability as a mediating variable, conducted on companies listed in the IDX Growth 30 during the 2020-2022 period. The data used in this study are secondary data, and the sampling technique is purposive sampling. The data sources for this research come from the Indonesia Stock Exchange and the official websites of the listed companies. The results of the study show that liquidity has a negative and significant effect on capital structure, liquidity has a positive and significant effect on profitability, profitability has a negative and significant effect on capital structure, profitability is able to mediate the relationship between liquidity and capital structure, firm size is able to moderate the relationship between liquidity and capital structure, firm size is able to moderate the relationship between profitability and capital structure, and liquidity affects capital structure mediated by profitability and moderated by firm size simultaneously.